Proton-coupled calcium transport by intact cells of Azotobacter vinelandii. - Barnes, E M (1980)
Addition of ionophores to resting aerobic cultures of Azotobacter vinelandii OP resulted in 45Ca2+ uptake (Km = 60 microM Ca2+; Vmax 1.1 nmol/min per mg of cell protein) which was inhibited by cations (La3+ greater than Mn2+ greater than Sr2+ greater Ba2+). The rate of Ca2+ entry correlated with the magnitude of a transmembrane proton gradient (inside acid) which developed in the respective order: valinomycin less than tetrachlorosalicylanilide less than nigericin less than gramicidin D less than tetrachlorosalicylanilide plus valinomycin. A process of calcium-proton exchange (antiport) is responsible for calcium accumulation under these conditions.